2022
DOI: 10.1002/cncr.34239
|View full text |Cite
|
Sign up to set email alerts
|

Critical impact of radiotherapy protocol compliance and quality in the treatment of retroperitoneal sarcomas: Results from the EORTC 62092‐22092 STRASS trial

Abstract: BACKGROUND:The European Organization for Research and Treatment of Cancer 22092-62092 STRASS trial failed to demonstrate the superiority of neoadjuvant radiotherapy (RT) over surgery alone in patients with retroperitoneal sarcoma. Therefore, an RT qualityassurance program was added to the study protocol to detect and correct RT deviations. The authors report results from the trial RT quality-assurance program and its potential effect on patient outcomes. METHODS: To evaluate the effect of RT compliance on surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Similarly, Peters and colleagues also observed that RT noncompliance was associated with a 20% decrement in overall survival at 2 years in a phase 3 head and neck cancer study 14 . The findings by Haas and colleagues in the current study are consistent with these prior reports 8 . Noncompliant RT plans were correlated with a less favorable ARFS and a trend toward poorer overall survival.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…Similarly, Peters and colleagues also observed that RT noncompliance was associated with a 20% decrement in overall survival at 2 years in a phase 3 head and neck cancer study 14 . The findings by Haas and colleagues in the current study are consistent with these prior reports 8 . Noncompliant RT plans were correlated with a less favorable ARFS and a trend toward poorer overall survival.…”
supporting
confidence: 88%
“…14 The findings by Haas and colleagues in the current study are consistent with these prior reports. 8 Noncompliant RT plans were correlated with a less favorable ARFS and a trend toward poorer overall survival. However, it was surprising that RT compliance was not associated with a lower rate of local recurrences.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…This flaw is particularly important if we think of the recent report from the STRASS RT quality-assurance program that showed a direct correlation between RT compliance and abdominal recurrence-free survival (ARFS) in patients treated in trial, or if we look at the growing evidence regarding the importance of the quality of surgery and center volume on surgical and oncological outcomes. 3,4 Third, information about post-surgical events different from patient death are not available. Thus, the direct effect of RT on local control or disease-specific survival are not measured.…”
mentioning
confidence: 99%